Gender-specific insights into TTN mutation: potential biomarker for female risk in kidney renal clear cell carcinoma - Ayan Saha; Senzuti Sharmin; Tazin Ahmed; Sadia Tabassum; Ayan Roy; Pallab Kar; Paromita Biswas; Jannatul Ferdoush (Journal of Genetic Engineering and Biotechnology)
Kidney Renal Clear Cell Carcinoma (KIRC) is a leading cause of cancer death worldwide, but its early detection remains hindered by a lack of genetic markers. Our study aims to find prospective biomarkers that could serve as prognostic indicators and help in the identification of efficient drug candidates for KIRC treatment. Importantly, this study identifies the hub genes that play a crucial role in KIRC and their impact on male and female patients. The cBioPortal was used to identify frequently mutated genes across seven KIRC studies. Additionally, GSE168845 was employed to identify the differentially expressed genes. The analysis revealed that the titin (TTN) gene was mutated and upregulated in KIRC. Subsequently, differential genes of wild-type TTN versus mutant TTN were identified using TNMplot. The NetworkAnalyst tool was used to conduct KEGG analysis and PPI analysis on these genes. Furthermore, the Kaplan-Meier Plotter was utilized to perform overall survival analysis. Our findings indicated that the TTN gene leads to poorer prognosis in women than in men. We also discovered that the female-specific prolactin signaling pathway plays a significant role in the progression of KIRC. Moreover, our study suggested that the GDF15 gene, involved in the prolactin signaling pathway, has a worse prognosis for KIRC in women than in men. Additionally, mRNA expression analysis showed a negative correlation between GDF15 and MAPK14 in KIRC. Collectively, our research indicates that TTN, GDF15, and MAPK14 can serve as prognostic biomarkers in female KIRC patients, offering prospects for enhanced treatment and patient outcomes in these cancers.